Structural, electrical and optical properties of AZO/SiO2/p-Si SIS heterojunction prepared by magnetron sputtering - HeBo; Ma, Zhong Quan; Jing, Xu; Lei, Zhao; Sheng, Zhang Nan; Feng, Li; Cheng, Shen; Ling, Shen; Jie, Meng Xia; Yue, Zhou Cheng; Shan, Yu Zheng; Ting, Yin Yan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
ZnO thin films doped with aluminum (AZO) were deposited on silicon dioxide covered type texturized Si substrates by radio frequency magnetron sputtering, to fabricate AZO/SiO2/p-Si heterojunction, as an absorber for ultraviolet cell. The microstructure, optical and electrical properties of the Al-doped ZnO films were characterized by XRD, SEM, UV-VIS spectrophotometer, current–voltage measurement, and four point probe technique, respectively. The results show that AZO films are of good quality. The electrical junction properties were investigated by I–V measurement, which reveals that the heterojunction shows rectifying behavior under a dark condition. The ideality factor and the saturation current of this diode are 24.42 and 8.92×10–5 A, respectively. And the values of IF/IR (IF and IR stand for forward and reverse current, respectively) at 10 V are found to be as high as 38. It shows fairly good rectifying behavior indicating formation of a diode between AZO and p-Si.
Optica Applicata, Vol. 40, 2010, nr 1, s. 15-24
Keywords: optyka; Al-doped ZnO (AZO); sputtering; SIS heterojunction; current–voltage (I–V) characteristics